Penggunaan dan Analisis Panel Surya Lepas Pantai Menggunakan Pipa Apung sebagai Media Apung - Nanda, Rizki Aulia; Gumelar, Agung; Mulyadi, Dodi (Badan Kerja Sama Teknik Mesin Indonesia, 2024)
Utilization of solar energy sources is one of the alternative energies to save fossil energy. The use of solar panels has been widely implemented in homes, buildings and open fields. Therefore, the largest energy source is on the beach, because the coastal area has an area without obstructions of sunlight. With this background, this study aims to create an offshore solar panel tool. The method used is to review literature studies, manufacture of offshore solar panels, testing on the beach and data analysis. The test results show that the average power versus time (Wh) produces the lowest value of 9.3679 Wh and a medium value of 23 Wh and the highest value of 26 Wh. The type of battery used is FLA (Flooded Lead Acid) with a voltage of 12V and a capacity of 5 Ah. The influence of the lowest and highest values ​​is the level of sunlight conditions on the beach from sunrise to sunset. Offshore solar panels can float well and receive good light energy sources.